Perlindungan Hukum Ekspresi Kreatif Manusia: Telaah terhadap Perlindungan Hak Kekayaan Intelektual dan Ekspresi Budaya Tradisional - M. Zulfa Aulia (Fakultas Hukum Universitas Islam Indonesia, 2007)
The discourse on the protection of the intellectual property rights (HKI) and the expression of traditional culture, is actually a discourse on the legal protection towards the expression of human’s creativity. Both of the intellectual property rights (HKI) and the expression of traditional culture are a form of the expression of human’s creativity, with only the difference between them is in the novelty. It is understood therefore, that there is dialectical relation between them on the legal protection towards the expression of human’s creativity. In such dialectical relation, the legal protection should also be addressed to the traditional culture, not merely on nowadays human creativity.